A New Risk-Scoring System for Colorectal Cancer and Polyp Screening - Romanová, Alexandra; Šťovíček, Jan; Brož, Jan (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Romanová A, Šťovíček J, Brož J. A new risk-scoring system for colorectal cancer and polyp screening. Turk J Gastroenterol. 2022;33(12):1079.